2017
DOI: 10.1038/s41598-017-03570-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Drying Methods for Recovery of Mushroom DNA

Abstract: Several methods have been reported for drying mushroom specimens for population genetic, taxonomic, and phylogenetic studies. However, most methods have not been directly compared for their effectiveness in preserving mushroom DNA. In this study, we compared silica gel drying at ambient temperature and oven drying at seven different temperatures. Two mushroom species representing two types of fruiting bodies were examined: the fleshy button mushroom Agaricus bisporus and the leathery shelf fungus Trametes vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Through the analysis of the effect of the four drying temperatures on the drying time and water loss ratio, we found that for all the drying temperatures, the fruiting bodies lost the majority of their water in the first 3 hr, and the water loss ratio decreased with the extension of drying time. This pattern was similar to the water loss reported in A. bisporus during HD (Wang, Liu, & Xu, 2017). Also, we found that for all the drying temperatures, the water loss ratio was the highest at the first 0.5 hr, the order of which was: 65℃ (40.15%)> 55℃ (28.97%)> 45℃ (25.57%)> 35℃ (22.96%).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Through the analysis of the effect of the four drying temperatures on the drying time and water loss ratio, we found that for all the drying temperatures, the fruiting bodies lost the majority of their water in the first 3 hr, and the water loss ratio decreased with the extension of drying time. This pattern was similar to the water loss reported in A. bisporus during HD (Wang, Liu, & Xu, 2017). Also, we found that for all the drying temperatures, the water loss ratio was the highest at the first 0.5 hr, the order of which was: 65℃ (40.15%)> 55℃ (28.97%)> 45℃ (25.57%)> 35℃ (22.96%).…”
Section: Resultssupporting
confidence: 89%
“…The color change of edible fungi during drying is an important index for selecting a drying method (Wang et al., 2017). The Yu Muer fruiting bodies have a milky‐white rough surface and a light yellow ventral surface.…”
Section: Resultsmentioning
confidence: 99%
“…The survival rate was calculated by counting the number of mycelial colonies (derived from treated or untreated germlings) after 3 days of incubation at 24°C. As previouslys reported (de Lima Alves et al, 2015; Wang et al, 2017), exposure to these two treatments induces water stress in fungal cells. Exposure of wild-type and mutant strains to 1.2 M sorbitol were performed following the procedure described below.…”
Section: Methodssupporting
confidence: 82%
“…Morphology and physiological parameter such as appearance, colour, dimension, spores and form of the fungus on media, with other environmental growth preferences is not sufficient for the identification of macrofungi. However, molecular based tools offer better alternatives for accurate identification (Akram et al 2012 ; Al-Habib et al 2014 ; Wang et al 2017 ) of wild medicinal and edible mushrooms, which will help in proper documentation and effective exploration. We have used the Internal transcribed spacer (ITS) sequence for the molecular identification of Calvatia gigantea .…”
Section: Resultsmentioning
confidence: 99%
“…Mushrooms have a long history of having been employed by humans as medicines for thousands of years (Ferreira et al 2010 ; Valverde et al 2015 ; Zhang et al 2016 ). Because they have been demonstrated to affect one or more target functions in the body, leading to either an improved state of health and well-being and/or reduction of risk of disease, they are referred to as functional foods (Guillamon et al, 2010 , Wang et al 2017 , Vamanu, 2018 ). Of the 14,000 to 15,000 species of mushrooms in the world around 700 of them have known medicinal properties (Lurie et al 2009 ; Li et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%